Isolation and Identification of Bacteria from Cattle Rumen Fluid and Their Application on In Vitro Digestibility of Rice Straw - Bira, Gerson Frans; Sio, Stefanus; Batu, Matius S; Pardosi, Lukas; Kia, Kristoforus W; kolo, Maria Magdalena; Nubatonis, Alfred (Animal Husbandry Study Program, Faculty of Agriculture, Timor University, 2025)
This study aimed to isolate and identify bacteria from the rumen fluid of Bali cattle and to evaluate their effect as microbial inoculants on the in vitro digestibility of rice straw. The experiment was conducted using a Completely Randomized Design (CRD) consisting of four treatments and four replications. The treatments included rice straw silage with the addition of 0%, 5%, 10%, and 15% of local microorganisms (MOL) derived from cattle rumen fluid. The observed variables included the isolation and identification of bacteria from the rumen fluid, and the assessment of in vitro digestibility, including Dry Matter Digestibility (DMD), Organic Matter Digestibility (OMD), Volatile Fatty Acid (VFA) concentration, and ammonia (NH₃) production. The results showed that the addition of rumen fluid MOL significantly (P<0.05) improved the digestibility parameters. The highest DMD (52.44%) and OMD (47.11%) were obtained from the treatment with 15% MOL. VFA and NH₃ concentrations also increased, indicating enhanced microbial activity and fermentation efficiency. The study concludes that MOL derived from cattle rumen fluid, particularly those containing Bacillus sp., is effective in improving the nutritional quality and digestibility of rice straw